Case Report: Spontaneous Intramural Hematoma of the Colon Secondary to Low Molecular Weight Heparin Therapy - Zhu, Ye; Wang, Chao; Xu, Chao; Liu, Jia (Frontiers in Pharmacology, 2021)
Background: Hematoma of the colon is a rare hemorrhagic complication that affects patients accepting low molecular weight heparin (LMWH) therapy. Only scarce cases of colon hematoma have been reported, usually in children or patients accepting warfarin therapy. Case summary: A 76-year-old Chinese man was diagnosed with atrial fibrillation and heart failure, with cardiac function NYHA grade III on March 21, 2018. This patient was given LMWH for anticoagulation therapy and developed a colon hematoma on the third day of hospitalization. Abdominal computed tomography (CT) showed the thickening of areas of the colon up to 110 mm × 78 mm in thickness, which was a symptom of colon hematoma. The patient underwent conservative treatment successfully. On March 27, the patient’s abdominal pain was alleviated, and a CT scan showed that the intestinal hematoma was absorbed. Conclusions: The most frequent minor bleeding events of LMWH anticoagulation are hemorrhage and subcutaneous hematoma. This case demonstrated that bowel hematoma despite its low incidence should be considered as an ADR of LMWH therapy, especially among patients who present with gastrointestinal symptoms.